Experimental and numerical investigation of combined convection heat transfer and fluid flow around circular cylinder through rectangular and trapezoidal open-cell aluminum foams - Mahdi, Raed Abed (Taylor and Francis Inc., 2015)
Combined convection heat transfer and fluid flow around a circular cylinder surface placed in open-fcell aluminum foams and subjected to constant heat flux inside a rectangular, water-filled horizontal channel was numerically and experimentally studied. Two models (rectangular and trapezoidal open-cell aluminum foam shapes) made of 6101-T6 alloy with pore densities of 10 and 40 pores per linear inch (PPI) and 7-9% relative density were employed as test sections. The aluminum foam dimensions were 35.7 x 35.7 x 36.85 mm, the Reynolds number range was 60-2000, and the modified Grashof number range was 2 x 10(2)-2.6 x 10(7). Governing equations (continuity, momentum, and energy) were solved using the finite-volume method (FVM). Effects of the porous characteristics of aluminum foams and mixed convection heat transfer parameters on buoyancy force, Nusselt number, friction factor, and pumping power values of the two models were investigated. The results show that high mixed convection occurred with the trapezoidal model. A high average Nusselt number value was obtained at 40PPI in the rectangular model. In the trapezoidal model, average Nusselt number decreased with increased aluminum foam pore density. Friction factor increased slightly with increasing modified Grashof number and decreased with increasing Reynolds number. Pumping power increased with increased pore density of aluminum foam and mixed convection parameters. The comparison shows good agreement between the numerical and experimental work and that the average results produced have an 8.02% deviation in average Nusselt number